Tendências da Engenharia de Materiais na sustentabilidade corporativa - Santos, Gabriela Camargo Fernandes dos (Universidade Federal de São Carlos, 2023)
Faced with environmental, social and economic challenges, there is a growing demand from the market and consumers regarding new attitudes in the corporate environment. Thus, companies are aware of the ESG (Environmental, Social, Governance) agenda, targeting guidelines such as reducing greenhouse gas emissions, concern for society such as diversity and inclusion of minorities, and data transparency for information security. In the environmental segment, there is currently a concern related to polymers, from their production to their numerous applications, due to the accumulation of waste in seas and oceans, damage to fauna and flora and even harm to human health. Solutions to these problems arise through the circular economy, with solid waste management, recycling processes, development of sustainable materials and monitoring impacts on the life cycle, functions that require knowledge of Materials Engineering, demonstrating the importance of the profession on this theme. The present work addresses the importance of the role of Materials Engineers and the possibilities of professional guidance in a career in sustainability for a person with this degree, if you are interested in the subject. From this, based on the reading of articles, analysis of plans for sustainable development of ESG-oriented companies and on interviews with people working in this segment, one sees a greater movement in relation to polymer packaging, since these are one of the predominant applications of plastics and with a shorter life cycle, being quickly discarded, considered “single use”. This type of application values polymer characteristics such as lightness, mechanical, chemical, thermal resistance, and variety of design, but does not consider the high durability aspect of this material, remaining many years in nature. Thus, the importance of the analytical character provided by the engineering course is evident, being essential a critical view from the resin to the disposal of the material. The direction of action is diverse and can range from data analysis, such as, for example, using life cycle analysis tools, to practical tasks with carrying out tests for the validation of materials and additives. Another point is related to the relevance of communication, it being essential to transmit information in a didactic way to avoid losses in the performance and disposal of the product made by the consumer. Therefore, knowledge of materials engineering significantly contributes to the ESG character in companies that produce or use polymeric materials.
Trends in Materials Engineering in corporate sustainability
Keywords: Sustentabilidade; ESG; Engenharia de Materiais; Polímeros; Sustainability; Materials Engineering; Polymers; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS